Egg protein derived ultralightweight hybrid monolithic aerogel for water purification. (October 2022) - Ozden, Sehmus; Monti, Susanna; Tozzini, Valentina; Dutta, Nikita S.; Gili, Stefania; Caggiano, Nick; Link, A. James; Pugno, Nicola M.; Higgins, John; Priestley, Rodney D.; Arnold, Craig B.
Graphical abstract: Abstract: The integration of 2D-graphitic carbon (G) with 1D-carbon nanofiber (CF) allows for the unique properties of 2D graphitic carbon to be combined with the low densities, mechanical performance, and high surface area required for applications across the energy and sustainability landscape. Through a combination of experiments and numerical modeling, we demonstrate the transformation of standard egg-white (EW) proteins into an ultralightweight G-CF aerogel with a multiscale structure. The resulting covalently-bonded hierarchical structure, derived from the complex underlying protein configuration, exhibits a density that is two orders of magnitude lower than existing state-of-the-art materials. We apply this material to the challenges of desalination and water purification, notably demonstrating that the G-CF aerogel significantly improves upon existing materials, capturing 98.2% of ionic impurities and 99.9% of nano/microplastic contamination from seawater.